2011
DOI: 10.3390/su3060789
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour Change in the UK Climate Debate: An Assessment of Responsibility, Agency and Political Dimensions

Abstract: This paper explores the politics around the role of agency in the UK climate change debate. Government interventions on the demand side of consumption have increasingly involved attempts to obtain greater traction with the values, attitudes and beliefs of citizens in relation to climate change and also in terms of influencing consumer behaviour at an individual level. With figures showing that approximately 40% of the UK's carbon emissions are attributable to household and transport behaviour, policy initiativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…Other authors argue that agencies should support socially responsible consumerism by providing information and education, sponsoring efficiency incentives, and modifying infrastructure. Findings show that individuals are more likely to find information campaigns to be relevant and meaningful if they are sponsored by local authorities than for-profit businesses [77,78].…”
Section: Customer Desire For Environmentally Friendly Products and Sementioning
confidence: 95%
See 1 more Smart Citation
“…Other authors argue that agencies should support socially responsible consumerism by providing information and education, sponsoring efficiency incentives, and modifying infrastructure. Findings show that individuals are more likely to find information campaigns to be relevant and meaningful if they are sponsored by local authorities than for-profit businesses [77,78].…”
Section: Customer Desire For Environmentally Friendly Products and Sementioning
confidence: 95%
“…Mandatory requirements may be required in residential markets, where reliance on consumer goodwill may be inadequate. In a survey of United Kingdom citizens, Fudge and Peters, 2010 [78] found that despite high awareness of the relationship between energy consumption, greenhouse gas emissions, and global warming, few individuals routinely made efforts to reduce energy in their daily lives. Respondents generally prioritized comfort and convenience over energy efficiency, indicating that information and education are not likely to be sufficient to induce behavioral changes.…”
Section: Customer Desire For Environmentally Friendly Products and Sementioning
confidence: 99%
“…They are thematic groups, organised nationally (and sometimes internationally) in relation to cross-cutting issues, rather than communities of place, with a local footing and day-to-day interactions between members. Some recent research suggests that the latter may lead to more immediate impacts on emissions (Centre for Sustainable Energy, 2007;Heiskanen, 2010;Peters et al, 2011). However, the two types of constituency are probably complementary.…”
Section: Providing Practical Opportunities For Public Engagement and mentioning
confidence: 99%
“…Similarly, Marques et al (2012) have shown that the recent reduction in CO 2 emissions through dieselisation has been surpassed by the increased kilometres driven in Europe. Consequently, a growing urgency in policy circles on the need for more effective strategies to reduce carbon emissions has seen the development of a stronger focus on behaviour change in the UK (Fudge and Peters 2011). For example, the UK Government's Community Action 2020-Together We Can encapsulated the increased focus on behaviour change, and in this regard, a Framework for Behaviour Change has also been developed (HM Government 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Road transport alone produces about 28 % of CO 2 in UK (Department for Transport 2010a), and 12 % of global CO 2 is produced from the personal road transport sector and is the only sector in which this trend is increasing (Anable et al 2012;Meyer et al 2007;Simpson 2006;Wadud et al 2008). As a result, the reduction in CO 2 emissions from the transport sector has been identified as a major challenge to these targets being met (Chapman 2007;Fudge and Peters 2011).…”
Section: Introductionmentioning
confidence: 99%